Examining parents’ intention to vaccinate their children in Pahang: The role of perceived severity, perceived susceptibility, and perceived barriers - Noor Amira Syazwani, Abd Rahman; Jamal Rizal, Razali; Mohd Rozaimy, Ridzuan; Ju, Soon Yew; Nur Hazirah, Hamdan (Penerbit UMPSA, 2024)
This study explores the impact of perceived severity, perceived susceptibility and perceived barriers on parents’ intention to vaccinate their children in Pahang, Malaysia, using the Health Belief Model (HBM). Vaccine hesitancy among parents presents unique challenges influenced by concerns about vaccine safety, misinformation and a lack of trust in healthcare systems. Implementing preventive measures to reduce infections and minimise severe consequences is crucial, especially among children. The study focuses on parents in Pahang and employs a quantitative research approach, collecting data through an online questionnaire. Analysis using descriptive statistics and partial least squares-structural equation modelling (PLS-SEM) is conducted based on responses from 372 participants. The findings demonstrate that parents’ perception of disease severity and susceptibility positively influences their intention to vaccinate their children. However, perceived barriers do not significantly affect vaccination intention, which is aligned with previous research. These results provide compelling evidence of the relationship between parents’ perception of disease severity, susceptibility and decision to vaccinate. The study highlights the role of parents’ perceptions in shaping their decision-making process. It reveals a significant correlation between parents’ perception of susceptibility and their intention to vaccinate, consistent with prior studies. Despite potential barrier such as concerns about vaccine safety, this research suggests that these perceived barriers minimally impact parents’ vaccination intention. These findings underscore the importance of addressing parents’ perceptions of disease severity and susceptibility to promote higher vaccination rates.